ANALYSIS OF ZERO PLASTIC BAG POLICY EFFECT ON GREEN BEHAVIOUR WITH STRUCTURAL EQUATION MODELING (SEM) METHOD - Indah, A.Besse Riyani; Syamsul, Nadzirah Ikasari; Retnari, Dian; Syamsul, Nilda (Center for Study and Journal Management FTI UMI, 2021)
Plastic bag is a product that is very often used in everyday life. Plastic bags are one of the biggest contributors to the volume of waste in Indonesia. Therefore, a policy related to the use of plastic bags is called a zero plastic bag. This policy requires plastic bag users to switch to using environmentally friendly bags. This study was conducted to analyze the effect of the zero platic bag policy on Makassar City community behavior related to the environment or green behavior if this policy is applied in the City of Makassar. To determine the effect of the zero plastic bag policy on people's behavior patterns about the environment using the SEM (Structural Equation Modeling) method. Initial identification was carried out by distributing questionnaires to respondents using plastic bags, especially retail consumers in Makassar City. The questionnaire contained green behavior variables which consisted of five variables. Then the results of data collection using a questionnaire are processed using descriptive analysis and then look for the effect of zero plastic bag policies on green behavior using the SEM method. The results of the identification of the influence of zero plastic bag policy based on four variables namely environmental knowledge, environmental attitude, green advertising, and green consumption on green behavior are that of the four variables that have a positive influence on green behavior are environmental attitude, green advertising, and green consumption . The results of this study can be used as policy input and see how effective this policy is when applied in Makassar City.